An Attempt at Alleviating Heat Stress Infertility in Male Broiler Breeder Chickens with Dietary Ascorbic Acid - McDaniel, C.D.; Hood, J.E.; Parker, H.M. (International Journal of Poultry Science, 2004)
Previous research regarding the effect of heat stress on broiler breeders is very limited. The objective of the present study was to determine the amount of ascorbic acid in the broiler breeders` diet that will improve reproductive performance of males that are exposed to continuous heat stress. One hundred forty-four Ross males (18 weeks old) were divided equally among six temperature controlled rooms. Three rooms were used for heat treatment and three rooms served as controls (21°C). The temperature in the heat treatment rooms was increased in two four-week phases followed by a final three week recovery phase with the temperatures for each period being 29 (mild stress), 32 (severe stress), and 21°C, respectively. The roosters in each room were equally divided among four dietary treatments consisting of 0, 250, 500, and 1000 ppm of ascorbic acid. Heat stress significantl/y decreased sperm quality index, sperm viability, and fertility. The percentage of dead sperm rose significantly during both the mild and severe heat phases and dropped immediately upon initiation of the recovery phase. Sperm motility decreased linearly with increasing ambient temperature but rebounded upon the removal of heat stress. The rate of fertilization was decreased as a result of heat stress. Dietary ascorbic acid did not improve any of the semen characteristics of control or heat stressed birds. Administration of 500 and 1000 ppm of dietary ascorbic acid resulted in a depression of fertility over each day postinsemination when the males were heat stressed. In conclusion, dietary ascorbic acid at the levels used in the present study did not improve the reproductive performance of broiler breeder males under normal or heat stress conditions.